The application of Raman spectroscopy for the detection and identification of microorganisms. (7th December 2015) - Stöckel, Stephan; Kirchhoff, Johanna; Neugebauer, Ute; Rösch, Petra; Popp, Jürgen
Abstract : A fast and reliable detection and identification of microorganisms is crucial in environmental science, for food quality as well as medical diagnosis. In these fields, all types of Raman spectroscopy are gaining more and more importance during the last years. The review provides an extensive overview of recent research, technical expertise, and scientific findings based on Raman spectroscopic detection and identification of microorganisms within the years 2010 and 2015, demonstrating the diverse capability of Raman spectroscopy as a modern analytical tool. Raman spectroscopy distinguishes itself from other currently applied techniques by its easy application at low cost, its high speed of analysis, and its broad information content on both the chemical composition and the structure of biomolecules within the microorganisms. Slight chances in the chemical composition of microorganisms can be monitored by means of Raman spectroscopy and used to differentiate genera, species, or even strains. Detection of pathogens is possible from complex matrices, such as soil, food, and body fluids. Further, spectroscopic studies of host–pathogen interactions are addressed as well as the effect of antibiotics on bacteria. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Raman spectroscopy for the investigation and identification of microorganisms is gaining more and more importance.